The current practices of New Zealand plastic surgeons with respect to the psychological well-being of patients seeking elective aesthetic procedures : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Albany, New Zealand - Hung, Mindy Min-Yu (Massey University, 2013)
The prevalence of psychopathology in patients seeking elective aesthetic surgery has been suggested to be higher compared to the general population, and adverse psychological outcomes appear to be more common than physical complications, particularly for patients with existing psychiatric problems. Although elective aesthetic surgery incorporates standard protocols to examine medical and anaesthetic risks, there seem to be no protocols for preoperative psychological evaluation. This study examines current practice among New Zealand plastic surgeons, their experience and management of their patients’ psychological well-being, and it compares data from New Zealand and USA. The participants were 25 surgeons in New Zealand eligible to perform elective aesthetic surgery who responded to an online survey. Statistical analysis was used to determine significant differences and relationships between variables. The majority of the surgeons in the sample relied mostly on their personal experience, intuition and clinical judgement for psychological evaluation. All the surgeons had at least some experience with patients presenting with psychological disorders, and some have had patients with adverse psychological outcomes after the surgery. Most of the surgeons refer patients with psychological issues to mental health care, however, a small number of surgeons found access to mental health care difficult. The preoperative consultation time was an important variable that was statistically related to the surgeon’s practice backgrounds and their experience of patients with psychopathology. In general, New Zealand data is consistent with those from USA in terms of the surgeons’ experience and practice. The findings suggest a need for preoperative psychological evaluation for elective aesthetic surgery in New Zealand.
Keywords: Plastic surgery; Psychological aspects; Plastic surgeons; Patients; New Zealand